An Analysis Of Sense Based Sentences In Khalil Gibran's Poems - Nugroho, Arif, Agus Wijayanto, Ph.D, Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
This research deals with sense based sentences in Khalil Gibran's poems.The aims of this research is to describe the types of sense based sentences in Khalil Gibran's poems and the illocutionary acts of sense based sentences found in poems written by Khalil Gibran. The type of this research is descriptive qualitative research. The writer uses poems written by Khalil Gibran as data source. The data of this research are simple declarative sentence. The writer employs documentation as method of collecting data with the techniques: reading, underlying or marking, and classifying the data. In analyzing data, the writer describes of sense based sentences by reffering to the theory of Hurford and Heasley (1983) and describing illocutionary acts of sense based sentences by Searle (1978). The result of this result shows that there are three types of sense based sentences from the forty two data (100%) found in Khalil Gibran's poems. They are analytic sentence (2 data/4, 76%), synthetic sentence (35 data/83, 33%), and contradiction sentence (5 data/11, 90%). The illocutionary acts is regretting, asserting or informing, expressing disappointment, complimenting, suggesting or advising, expressing anger, expressing pride, annoying, convincing, remainding, expressing doubt, amazing, rejecting, condoling, and warning.